Partnership as Student Power: Democracy and Governance in a Neoliberal University - Cornelius-Bell, Aidan; Bell, Piper A. (Radical Teacher, 2020)
In the wake of Flinders University’s radical organisational restructure, we reflect on what guided the decisions and process, namely a neoliberal understanding and framing of higher education and corporal, top-down managerial systems. We explore this current climate of the neoliberal university and argue that student power is once again needed to shift the conception of university ‘success’ back into a democratic form of governance. However, rather than student power constituting of a traditional 1970s form of picketing protests, we argue that a model of working within current structures is prudent. Partnership with students initiatives provide unexpected hope for student participation in rebuilding the conception of the democratic university as a public good, but also highlight the relevance of student ‘activism’ in 2019.